The effect of modification of sympathetic activity on responses to ligation of a coronary artery in the conscious rat. - Botting, J. H. (Nature Publishing Group, 1983)
1 Ligation of a coronary artery was performed in conscious rats whose sympathetic system activity had been altered by various treatments. 2 beta-Adrenoceptor blockade with acute (0.2 mg kg-1 plus 0.1 micrograms kg-1 min-1) or chronic (50-60 mg kg-1 daily for 12 days) propranolol treatment had little effect on arrhythmias, or other responses to ligation. 3 Abrupt withdrawal of chronic propranolol two days before ligation was also without effect. 4 Reduction of sympathetic activity acutely with labetalol (5 mg kg-1), or chronically with adrenomedullectomy and 6-hydroxydopamine treatment, accentuated the adverse effects of ligation. 5 The results of this study suggest that, while activity of the sympathetic system is not detrimental during ligation in the conscious rat, it may be important for survival.